Health workforce management during the COVID 19 pandemics - Ignjatović, Milica; Gavrić, Gordana; Jovčić, Ljiljana (Industrija, 2024)
After dealing with the growing number of infected health workers in the province of Hubei in China, it was concluded that the most important link in the fight against SARS - CoV - 2 infection is the proper and responsible management of health personnel. The aim of the paper is to show, with the help of research, how state health institutions in our country manage their employees during the pandemic, with the intention of finding oversights and giving recommendations so as to improve the management of health workers. Discovering the critical points of health workers management is very important in order to raise the overall quality of health services in the future in emergency situation. A total of 150 respondents employed in COVID hospitals in Belgrade and Loznica took part in this research. The results of the research obtained using the descriptive analysis methods, showed that the management of employees has to be at a higher level, with a special emphasis on the improvement of management of health of the employees and their safety at work.